Software module for automatic correction of drawings obtained as a result of graphic data exchange between CAD systems, using the furniture production example - A. V. Kalinichenko; A. Yu. Alikov; T. A. Yurosheva (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. When designing complex objects, as well as when it is necessary to perform export-import operations between various computer-aided design systems, the task of automatic correction of drawings becomes quite relevant. Development of a software module for automatic correction of drawings in the AutoCAD system, the need for which is due to reasons such as: the use of different file formats for storing drawings by different CAD systems, the complexity of the drawings. Method. As part of the study, methods of geometric modeling, analytical geometry and graphical presentation of results were used. Result. Algorithms for automatic correction of parameters of position and outline of drawing fragments in the AutoCAD system have been developed, with complexity of O(n) and O(n2 ). Conclusion. Analysis of the functionality of the developed module allows us to assert that its use will reduce the time spent when correcting drawings obtained as a result of import from other CAD systems in the AutoCAD system, and improve the quality of design documentation.